The effects of psychological stress on T-lymphocyte subsets and immunity globulin in athletes of different personality characteristics - Huang, W.; Wu, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to discover the influence of psychological stress on immune function of different personality characteristic of teenager shooters. Summary: The acute short-time psychological stress restrained the function both in the humoral immunity and cellular immunity in teenager shoot athletes. This research suggests that the nervous system possibly adjusts immunoreactions. It enriches theories of Psychoneuroimmunology. As this study is originated in Physical Education field, the result will boost the application of Psychoneuroimmunology on Physical Education.